Association of pan-immune inflammation value and lung health in adults - Ya Lin; Xiao Lin; Chufan Ren; Lanlan Song; Chao Gu (BMC Pulmonary Medicine)
Abstract Background Lung health is intricately linked with inflammation. The pan-immune-inflammation value (PIV) emerges as a promising biomarker, offering reflection into systemic inflammatory states and assisting in the prognosis of diverse diseases. This research aims to explore the associations between PIV and respiratory symptoms, respiratory diseases and lung function. Methods The study was a cross-sectional population study from the National Health and Nutrition Examination Survey (NHANES). Restricted cubic spline (RCS) models were conducted to explore the relationships between PIV and respiratory health outcomes, while weighted linear regression models and weighted logistic regression models were the ones used for regression analysis. Trend tests probed the evolving relationship among PIV quartiles and outcomes. The study incorporated subgroup analysis and interaction tests to examine associations within specific subpopulations. Results From the cohort of 6,263 participants, a distinct negative correlation was identified between PIV and lung health. Subsequent to confounding factors, a 100-unit increment in PIV was linked to a 2% increase in the incidence of cough and phlegm (OR, 95% CI: 1.02, 1.00 to 1.05; 1.02, 1.00 to 1.04). Additionally, higher PIV was associated with reductions in FEV1 (MD, 95% CI: -5.37, -9.10 to -1.64) and FVC (MD, 95% CI: -5.75, -10.34 to -1.15). Categorizing PIV into quartiles revealed an ascending trend: A significantly higher risk of cough/phlegm/wheeze was found in participants in the second/third/fourth PIV quartile compared to those in the first PIV quartile (all p for trend < 0.05). Moreover, lung function indicators (FEV1, FEV1%, FVC, FVC%, FEV1/FVC) declined significantly in the fourth quartile (all p for trend < 0.05). Besides, a nonlinear relationship between PIV and outcomes was evident. Subgroup analysis revealed variations in these associations stratified by gender, age, smoking and drinking status, as well as certain disease history. Conclusions The study highlighted the potential connections between PIV and respiratory symptoms, respiratory diseases and lung function. Monitoring PIV level could provide valuable insights into the inflammatory status and may inform clinical approaches for managing respiratory health.